Effects of supplementation of Bacillus amyloliquefaciens on performance, systemic immunity, and intestinal microbiota of weaned pigs experimentally infected with a pathogenic enterotoxigenic E. coli F18 - Jinno, Cynthia; Wong, Braden; Klünemann, Martina; Htoo, John; Li, Xunde; Liu, Yanhong (Frontiers in Microbiology, 2023)
The objective of this study was to investigate the effects of dietary supplementation of Bacillus (B.) amyloliquefaciens on growth performance, diarrhea, systemic immunity, and intestinal microbiota of weaned pigs experimentally infected with F18 enterotoxigenic Escherichia coli (ETEC). A total of 50 weaned pigs (7.41 ± 1.35 kg BW) were individually housed and randomly allotted to one of the following five treatments: sham control (CON-), sham B. amyloliquefaciens (BAM-), challenged control (CON+), challenged B. amyloliquefaciens (BAM+), and challenged carbadox (AGP+). The experiment lasted 28 days, with 7 days of adaptation and 21 days after the first ETEC inoculation. ETEC challenge reduced (P < 0.05) average daily gain (ADG) of pigs. Compared with CON+, AGP+ enhanced (P < 0.05) ADG, while B. amyloliquefaciens supplementation tended (P < 0.10) to increase ADG in pigs from days 0 to 21 post-inoculation (PI). The ETEC challenge increased (P < 0.05) white blood cell (WBC) count on days 7 and 21 PI, while BAM+ pigs tended (P < 0.10) to have low WBC on day 7 PI and had lower (P < 0.05) WBC on day 21 PI compared with CON+. In comparison to AGP+ fecal microbiota, BAM+ had a lower (P < 0.05) relative abundance of Lachnospiraceae on day 0 and Clostridiaceae on day 21 PI, but a higher (P < 0.05) relative abundance of Enterobacyeriaceae on day 0. In ileal digesta, the Shannon index was higher (P < 0.05) in BAM+ than in AGP+. Bray-Curtis PCoA displayed a difference in bacterial community composition in ileal digesta collected from sham pigs vs. ETEC-infected pigs on day 21 PI. Pigs in BAM+ had a greater (P < 0.05) relative abundance of Firmicutes, but a lower (P < 0.05) relative abundance of Actinomycetota and Bacteroidota in ileal digesta than pigs in AGP+. Ileal digesta from AGP+ had a greater (P < 0.05) abundance of Clostridium sensu stricto 1 but lower (P < 0.05) Bifidobacterium than pigs in BAM+. In conclusion, supplementation of B. amyloliquefaciens tended to increase ADG and had limited effects on the diarrhea of ETEC-infected pigs. However, pigs fed with B. amyloliquefaciens exhibit milder systemic inflammation than controls. B. amyloliquefaciens differently modified the intestinal microbiota of weaned pigs compared with carbadox.